Pengaruh Network Behavior Terhadap Venture Performance Dengan Social Capital dan Tacit Knowledge Sebagai Variabel Mediasi - Dandi , Dandi; Muhar, Ani Muwarni; Nahrisah , Ezzah (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This Study aims to determine the effect of Network Behavior on Venture Performance with Tacit Knowledge as variable mediating on small business in Percut Sei Tuan district. The methods analysis using regression analysis and kausal step methods used to know the effect between variable independent and variable dependent with mediating by variable mediating. The type of data used in this research is assosiative with paradigm quantitative. The population and sample in this study is the all of small business in Percut Sei Tuan district amount 295 business with 170 business as sample.The Results showed that variable Network Behavior has a positive and significant effect on variable Venture Performance. Variable Social Capital has a significant effect on variableVenture Performance, also variable Tacit knowledge has a significant effect on variable Venture Performance.